Determination of the stripping process of asphalt mixtures and the effective mix design and SFE parameters on its different phases. (20th July 2019) - Esmaeili, Niloofar; Hamedi, Gholam Hossein; Khodadadi, Mojtaba
Highlights: The stripping process of HMA mixtures consisted of two phases with different intensities. The stripping occurs with different rate two stages of stripping process. SFE and mix design parameters were effective factors in the first phase. SFE and mix design parameters were effective factors in the second phase. Abstract: In the present study, attempts were made to determine the process and different phases of stripping by conducting repeated load tests on 24 different asphalt mixtures and specify the effect of thermodynamic (free energy of adhesion, free energy of cohesion, and debonding energy) and mix design parameters (specific surface area of aggregates, asphalt film thickness, and permeability) on different phases of the process. The results revealed that the stripping process consisted of two separate phases with varying intensities and mechanisms. Free energy of cohesion and the debonding energy had the most significant effect on the rise and decline of loading cycles to the initial stripping point, respectively. In the phase after the initial stripping point where the system's tendency to stripping grew even higher, the specific surface area of aggregates and the debonding energy had the greatest impact on the decrease and increase of the stripping rate respectively.